PENATAAN ARSIP DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN NATUNA - Hasmardiyati E.21108098 (FISIP Universitas Tanjungpura, 2013)
Research topic was chosen because it is the center of the field of archival information that is contained in an organization. The implementation of a good filing system is the organizational support for accomplishing the goal. Therefore, the filing must be managed properly. Archival storage system in a way that is neat and tidy at the right place will affect the effectiveness of service and increase employee productivity. Results of research in the Department of Population and Civil Registration Natuna regency shows that the system accuracy primarily archival arrangement and placement of store archive, it is good enough and neatly arranged, performed in a centralized archive storage, making it easier for officers to find the archive file the required return. Keywords: Structuring archives, accuracy, placement and archival storage.